Wasps (Hymenoptera: Chalcidoidea) associated with galls in seed-capsules of Eucalyptus camaldulensis (Myrtaceae) in South Africa : species composition, trophic relationships and effects - Klein, Hildegard (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 94-107).